Exosomes derived from ALR-modified adipose mesenchymal stem cells mediate hepatoprotective effects on hepatic ischemia–reperfusion injury by promoting regeneration and protecting mitochondria - YaJun Ma; Tao Liu; Pujun Li; Lei Cao; Xiangyu Lu; HongBin Wang (Stem Cell Research & Therapy)
Abstract Background Exosomes are rich in bioactive molecules. Their unique lipid bilayer structure gives them the advantages of protecting the contents from degradation, easy cellular uptake, and good passive targeting. MSC-derived exosomes, which are natural vesicles ideal for gene delivery, exhibit a broad spectrum of therapeutic benefits. Methods In this study, which combines cell-free therapy with gene therapy, adipose mesenchymal stem cells (ADSCs) were genetically modified with augmenter of liver regeneration (ALR) to derive exosomes overexpressing ALR, which were used as therapeutic agents in a miniature porcine model of laparoscopic hepatic ischemia‒reperfusion injury (IRI) combined with partial hepatectomy injury. Results The findings of this study demonstrated that ALR-overexpressing adipose mesenchymal stem cell-derived exosomes (ADSC-Exo) ameliorate hepatic tissue injury, reduce apoptosis, promote hepatic regeneration, and protect the integrity of the cellular mitochondrial structure and function. Conclusions In conclusion, ALR gene-modified ADSC-Exo strongly attenuate liver injury and promote liver tissue repair.